Machinery in the United States, Sweden and Germany: An assessment of changes in comparative advantage - Frank Dietmar Weiss; Frank Wolter (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1974)
Since the early sixties traditional machinery suppliers, almost exclusively located in highly advanced economies, have been subject to considerable adjustment pressures. Among the most important causes, firstly, was the increasing international penetration of markets among traditional machinery suppliers % secondly, Japan emerged as a vigourous competitor; and thirdly, a number of semiindustrialized countries established mechanical engineering industries of their own which in certain activities even proved capable of successfully competing on the world market. As these events have affected and still affect the international division of labour in the machinery industry, the future role of machinery in highly advanced economies may become somewhat uncertain, particularly as the establishment of machinery industries in developing countries continues. In order to obtain an understanding of implications for the high-income countries, we shall focus on the recent development of machinery in the United States, Sweden, and the Federal Republic of Germany. These countries have been selected for investigation because they belong to the most advanced economies in the world but differ in the size of their domestic market and in their structure of production. Analyzing these countries, the purpose of this paper is firstly, to specify determinants of location for the machinery industry as a whole, and secondly to identify individual branches of machinery, if any, in which these highest-income countries are tending to lose their competitiveness. In part I a multi-country cross-section analysis is undertaken to determine a normal pattern of development for the machinery industry. For the United States, Sweden, and Germany deviations from this normal pattern are used to diagnosticize country-specific idiosyncracies. Besides this, the normal pattern itself has useful prognostic properties. Part II discusses some determinats of location. Changes in relative factor absorption,. as well as economies of scale and national idiosyncracies are examined for their implications on the high-income countries as advantageous locations for the machinery industry. Part III applies the concept of revealed comparative advantage to 36 sub-industries of machinery.
Keywords: 330